Para-tricipital approach for extra articular fractures of the distal humerus: a case series - Rashid, Rasiq; Beigh, Imtiyaz Ahmad; Khan, Shahid Shabir; Dar, Reyaz Ahmad; Maajid, Saheel (International Journal of Research in Orthopaedics, 2023)
Extra-articular fractures of the distal humerus are frequently managed surgically as these fractures are often unstable and have associated radial nerve injury. Different surgical approaches can be used to fix this fracture. We operated on a series of 9 patients with extra-articular fractures of the distal humerus utilizing the para-tricipital approach. Clinical outcomes were assessed by Mayo elbow performance score and visual analog scores. Radiological outcomes were assessed by plain radiographs. Time to union was an average of 4.2 months. Mean range of motion achieved at final follow-up was 122.50. Mean Mayo elbow performance score was 92.4. Excellent clinical results can be achieved by utilizing para-tricipital approach in extra-articular fractures of the distal humerus. Besides providing adequate exposure for rigid fracture fixation, this approach prevents the morbidity associated with triceps injury.